BIODIVERSITAS MANGROVE DI DESA KUTA KECAMATAN KANATANG DAN IMPLIKASINYA SEBAGAI SUMBER BELAJAR FLIPBOOK - Paji Maji, Ningsi; Tamu Ina, Anita; Meissy Matulessy, Yoin (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the diversity of mangrove species in Kuta Village, Kanatang District, East Sumba, and their use as a digital learning resource in the form of a flipbook. The method used in this study was the transect line plot method by creating double transect plots on each observation transect and establishing three plots/squares measuring 20 m x 20 m with a distance of 20 meters between plots to observe tree-level mangroves, plots measuring 10 m x 10 m to observe stump-level mangroves, and plots measuring 5 m x 5 m for seedling level. The study found a mangrove species composition comprising 5 families, 5 genera, and 9 species, with a total of 337 individuals, including 237 tree-level individuals, 68 stump-level individuals, and 32 seedling-level individuals. The mangrove species identified were Rhizophora mucronata, Rhizophora apiculata, Rhizopora stylosa, Sonneratia alba, Sonneratia ovata, Avicennia alba, Bruguiera gymnorrhiza, Aegiceras corniculatum, and Scyphiphora hydrophyllaceae. The diversity index at the tree growth level was 1.9518, the stake level was 2.0496, and the seedling level was 1.9588, which means that the diversity of mangrove species is moderate. The flipbook validation results obtained from subject matter experts were 100% and fell into the highly suitable category, while the validation results from media design experts were 89.58% with a suitable category, meaning that this flipbook can be used as a digital learning resource in schools.